Improved 123I-Ioflupane Binding After Immunotherapy in Anti–NAE Antibody–Positive Hashimoto Encephalopathy That Clinically Mimicked Multiple System Atrophy. (August 2017) - Otsuka, Juuri; Hida, Ayumi; Ogyu, Kamiyu; Minamimoto, Ryogo; Takeuchi, Sousuke
Abstract : Abstract: We describe an 84-year-old man with anti–NH2-terminal of α-enolase antibody–positive Hashimoto encephalopathy that clinically mimicked multiple system atrophy who underwent investigation by dopamine transporter SPECT before and after immunotherapy. Before treatment, dopamine transporter SPECT showed reduced striatal 123 I-ioflupane binding, with a mean specific binding ratio of 2.42, even though he had no apparent parkinsonism. After immunotherapy, mean specific binding ratio was improved to 3.22. Dopamine transporter SPECT was useful in this case to detect subclinical striatal dysfunction, and evaluation both before and after immunotherapy helped to distinguish between neurodegenerative disease and neuroimmunological disorder.